"Imagining a More Just World": Interview with Julie Maldonado. Issue 1 (29th July 2020) - Maldonado, Julie; Schuller, Mark; Benedeck, Lacey; Boddy, Halle; Kramer, Katelyn; Blankenberger, Evan; Cieslak, Ardyn; Jenkins, Christine
Abstract: It is difficult to canonize anthropology and anthropological concepts, in part because of the creative tensions within the discipline's contradictions: a desire and deep respect for local knowledge with a global, comparative perspective, what might be called the "anthropological imagination." Firmly rooted in—and in defense of—an inclusive vision of humanity, an anthropological imagination inspires "radical empathy." It offers the scaffolding of a coalitional politics that values the specificity of local struggles but also reaffirms and defends humanity. We must identify the humanity in others, and the common humanity in their struggle, while affirming particular identities and challenging differential privilege: an anthropological imagination inspires radical empathy and solidarity, reminding us, in the words of the World Social Forum, that "another world is possible." How people learn to cultivate this anthropological imagination and bring it in the service of marginalized groups is not generally discussed, and rarely taught. This article aims to bridge this gap. On October 10, 2018, Julie Maldonado, Associate Director for the Livelihoods Knowledge Exchange Network (LiKEN), discussed her new book, Seeking Justice in an Energy Sacrifice Zone: Standing on Vanishing Land in Coastal Louisiana, via video‐conference with Mark Schuller's Anthropology and Contemporary World Problems class at Northern Illinois University. This interview offers one perspective of a career focused around advocacy anthropology that aims to reach public audiences and policy‐ and decision‐makers in ways that translates scholarly research into information that is most useful for problem solving and enacting change in response to our climate crisis.